2018
DOI: 10.1161/circulationaha.118.033703
|View full text |Cite
|
Sign up to set email alerts
|

Gata4-Dependent Differentiation of c-Kit + –Derived Endothelial Cells Underlies Artefactual Cardiomyocyte Regeneration in the Heart

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 60 publications
2
36
1
Order By: Relevance
“…Mishra et al have demonstrated that progenitor cells isolated from the atria of patients with congenital heart disease showed the highest expression of the stem cell markers c-kit and Nkx2.5 in the neonatal age group (compared to infants and older children), and that this cell content directly correlated to their regenerative potential in mouse infarct models [ 5 ]. Recent work using kit allele lineage tracing has questioned the capacity of c-kit-positive CPCs to generate de novo cardiomyocytes [ 6 ], indicating instead that endothelial cells represent the principal fate of kit lineage-traced cells [ 7 ]. On the other hand, Ellison et al provided evidence based on genetic murine models and cell transplantation experiments that endogenous c-kit-positive cells cardiac stem cells are capable of generating new cardiomyocytes that are necessary and sufficient for myocardial repair [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mishra et al have demonstrated that progenitor cells isolated from the atria of patients with congenital heart disease showed the highest expression of the stem cell markers c-kit and Nkx2.5 in the neonatal age group (compared to infants and older children), and that this cell content directly correlated to their regenerative potential in mouse infarct models [ 5 ]. Recent work using kit allele lineage tracing has questioned the capacity of c-kit-positive CPCs to generate de novo cardiomyocytes [ 6 ], indicating instead that endothelial cells represent the principal fate of kit lineage-traced cells [ 7 ]. On the other hand, Ellison et al provided evidence based on genetic murine models and cell transplantation experiments that endogenous c-kit-positive cells cardiac stem cells are capable of generating new cardiomyocytes that are necessary and sufficient for myocardial repair [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies reporting some key TFs of cardiac regeneration validated via observation of heart regeneration after manipulating the corresponding gene expression in a myocardial infarction mouse model or in a cardiac apex resection mouse model (Tao et al, ; Xiang et al, ; Maliken et al, ). TBX20 is one of these known key TFs of cardiac regeneration, and we also identified this protein in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, c-kit was used as a cardiac progenitor cell marker [ 116 , 117 ]. Recently, several studies revealed that the contribution of c-kit+ cells to the generation of cardiomyocytes is insignificant due to their heterogeneous nature [ 117 , 118 , 119 ].…”
Section: Genetically Modified Stem Cell For MI Treatmentmentioning
confidence: 99%